Financial Sector Assessment Program : Brazil - Basel Core Principles for Effective Banking Supervision - International Monetary Fund; World Bank (World Bank, Washington, DC, 2013)
Brazil has a well-defined banking supervision process supported by a legal framework that grants the Banco Central do Brasil (BCB) broad enforcement powers for corrective action and weak bank resolution. This assessment of the Basel Core Principles (BCP) for effective supervision was conducted from February 27 through March 20, 2012. As agreed with the authorities, the supervisory framework was assessed against the BCP methodology issued by the Basel Committee on Banking Supervision (BCBS) in October 2006. In self-assessment the authorities addressed both essential and additional criteria and the assessors based their conclusions on compliance with both criteria. The last BCP assessment was conducted in 2002, however, the grading is not comparable to this assessment as the principles and methodology were revised in 2006. Although the BCB operates on an independent mode, there are amendments to Law 4595-1964 (banking law) that will aid in protecting the continuation of the operational independence.